2013
DOI: 10.1111/1755-0998.12135
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c oxidase I primers for corbiculate bees: DNA barcode and mini‐barcode

Abstract: Bees (Apidae), of which there are more than 19 900 species, are extremely important for ecosystem services and economic purposes, so taxon identity is a major concern. The goal of this study was to optimize the DNA barcode technique based on the Cytochrome c oxidase (COI) mitochondrial gene region. This approach has previously been shown to be useful in resolving taxonomic inconsistencies and for species identification when morphological data are poor. Specifically, we designed and tested new primers and stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 46 publications
0
36
0
6
Order By: Relevance
“…We extracted total DNA from the middle leg of one individual per nest (sampling site in the case of Bagé) according to the methodology proposed by Walsh et al (1991). We performed a PCR using conditions previously described (Françoso and Arias 2013;Simon et al 1994). For the PCR, it was used 5 μl of DNA, 2 μl of each primer (10 pmol), 25 μl of 2× Promega PCRMaster Mix [Taq-DNA polymerase (0.05 units/μl), 2× reaction buffer, 400 μM of each dNTP, and 3 mM of MgCl 2 ], and 16 μl of ultra-pure water.…”
Section: Molecular Analysismentioning
confidence: 99%
“…We extracted total DNA from the middle leg of one individual per nest (sampling site in the case of Bagé) according to the methodology proposed by Walsh et al (1991). We performed a PCR using conditions previously described (Françoso and Arias 2013;Simon et al 1994). For the PCR, it was used 5 μl of DNA, 2 μl of each primer (10 pmol), 25 μl of 2× Promega PCRMaster Mix [Taq-DNA polymerase (0.05 units/μl), 2× reaction buffer, 400 μM of each dNTP, and 3 mM of MgCl 2 ], and 16 μl of ultra-pure water.…”
Section: Molecular Analysismentioning
confidence: 99%
“…[29]) and insects (e.g. [30]). More interestingly, in most studies using this partition of the CO1 gene, taxon specific primers have been used instead of the universal primers established by Folmer et al in 1994 [2932].…”
Section: Introductionmentioning
confidence: 99%
“…To remove the phylogenetic effects from the analysis of data, we built a phylogeny of Meliponini species mainly based on the genetic information available on the GenBank. This genetic information involved partial sequences of two mitochondrial loci (cytochrome oxidase subunit I, COI; and 16S ribosomal RNA, 16S) and four nuclear loci (arginine kinase, ArgK; elongation factor 1 alpha, EF‐1α; long‐wavelength rhodopsin, LWR; and 28S ribosomal RNA, 28S) that were used in previous phylogenetic studies in stingless bees (Françoso & Arias, ; Halcroft et al, ; May‐Itza, Quezada‐Euán, Medina, Enríquez, & De la Rúa, ; Ramírez et al, ; Rasmussen & Cameron, ; Ruiz, May‐Itza, Quezada‐Euán, & De la Rúa, ). Particularly, COI sequences for three Meliponini species ( Frieseomelitta nigra , Lestrimelitta niitkib , and Partamona bilineata ) were provided by the Canadian Barcode of Life Network.…”
Section: Methodsmentioning
confidence: 99%
“…To remove the phylogenetic effects from the analysis of data, we built a phylogeny of Meliponini species mainly based on the genetic information available on the GenBank. This genetic information involved partial sequences of two mitochondrial loci (cytochrome oxidase subunit I, COI; and 16S ribosomal RNA, 16S) and four nuclear loci (arginine kinase, ArgK; elongation factor 1 alpha, EF-1α; long-wavelength rhodopsin, LWR; and 28S ribosomal RNA, 28S) that were used in previous phylogenetic studies in stingless bees (Françoso & Arias, 2013;Halcroft et al, 2016 we first homologated the taxonomic information found in the literature search with the updated revision by Camargo and Pedro (2007) and Rasmussen and Cameron (2010). We also retrieved from GenBank genetic information of five corbiculate bee species (Apis…”
Section: Phylogenetic Reconstructionmentioning
confidence: 99%